Renal Effects of Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers in Patients with Liver Cirrhosis: A Nationwide Cohort Study - Wei-Fan Hsu; Shi-Hang Yu; Jaw-Town Lin; Jaw-Ching Wu; Ming-Chih Hou; Yi-Hsiang Huang; Chun-Ying Wu; Cheng-Yuan Peng (Gastroenterology Research and Practice)
Background. The use of angiotensin-converting enzyme inhibitors (ACEis) and angiotensin receptor blockers (ARBs) carries a risk of renal function deterioration in cirrhotic patients with ascites. However, whether the long-term use of ACEis/ARBs is safe in cirrhotic patients without ascites remains unknown. Methods. In this nationwide cohort study, we identified 311,361 newly diagnosed cirrhotic patients between January 1997 and December 2013. To avoid indication and immortal time biases, patients receiving regular ACEi/ARB therapy, defined as the ACEi/ARB cohort, were matched to patients receiving regular calcium channel blockers (CCBs), defined as the CCB cohort, at a ratio of 1 : 1 by age, sex, and propensity scores for comorbidities and medications (2,188 patients in each cohort). Cumulative incidence rates and multivariate analyses of end-stage renal disease (ESRD) risk were adjusted for competing mortality. Results. The 10-year cumulative incidence rates of ESRD were 2.32% (95% confidence interval [CI]: 1.45–3.20) in the ACEi/ARB cohort and 1.70% (95% CI: 1.03–2.36) in the CCB cohort (P=0.610). In multivariate analyses, ACEi/ARB use was not associated with a higher risk of ESRD in cirrhotic patients (hazard ratio HR=1.15; 95% CI: 0.69–1.94, P=0.591). In the sensitivity test, the 10-year cumulative incidence rates of ESRD in cirrhotic patients with ascites were 6.50% (95% CI: 0.54–12.46) and 1.24% (95% CI: 0.00–2.71) in ACEi/ARB and CCB cohorts, respectively (P=0.090). Conclusions. Long-term ACEi/ARB use was not associated with a higher risk of ESRD in cirrhotic patients. However, the risk of ESRD tended to increase in cirrhotic patients with ascites.